Hvorfor ble kirkegårder velsignet? - Jensenius, Jørgen H. (Hikuin, 2000)
Why were churchyards blessed? By Jørgen H. Jensenius The question asked in this article is why churches were dedicated and churchyards were solemnly blessed in the Middle Ages. Five possible reasons are proposed. Firstly, because a possible pagan place of worship had to be purified by exorcism and blessing before it was suitable for Christian worship. Secondly, because a priest was not allowed to celebrate mass in a church before the altar was dedicated to God in the name of a Saint. By this action the whole place was reserved for Christian worship perpetually. Thirdly, because the dedication ceremony was meant to create awe and respect for the holy place so fugitives seeking sanctuary should be left unharmed. Fourthly, because the public and circumstantial rite was meant to make visible the transfer of property and the new property boundaries. Finally, because the ritual should inculcate into the public respect for the property of the Church. Dedication of churches and solemnly blessing of churchyards were therefore both mean and aim. The aim was to promote respect for the site and the people residing there. The mean was to create awe by connecting it to holiness. In a predominant oral culture this had to be done by actions and statements.